2020
DOI: 10.1590/s1984-29612020091
|View full text |Cite
|
Sign up to set email alerts
|

External and gastrointestinal parasites of the Franklin’s Gull, Leucophaeus pipixcan (Charadriiformes: Laridae), in Talcahuano, central Chile

Abstract: Parasitological studies of the Franklin's gull, Leucophaeus pipixcan, are scarce, and knowledge about its endoparasites is quite limited. In order to describe its parasitic community, a total of 60 Franklin’s gulls were captured in the coastal area in central Chile, using modified Bal-chatri traps. Ectoparasites were collected from all 60 live individuals through inspection of their plumage, while 30 were examined for endoparasites by standard parasitological necropsy. The prevalence of ectoparasites was 78.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
2
1
0
Order By: Relevance
“…In our study, we confirmed the presence of this louse subspecies in hosts of the genus Chroicocephalus, but with a presence on the back rather than on the wings as reported by González-Acuña et al (2020).…”
Section: Phthirapterasupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we confirmed the presence of this louse subspecies in hosts of the genus Chroicocephalus, but with a presence on the back rather than on the wings as reported by González-Acuña et al (2020).…”
Section: Phthirapterasupporting
confidence: 90%
“…Saemundssonia lari is a cosmopolitan species that parasitizes a very large number of Franklin's Gull, Leucophaeus pipixcan Wagler, 1831 (Price et al 2003). This species prefers the head and neck, which has already been reported in previous articles (Yamagishi et al 2014;González-Acuña et al 2020).…”
Section: Phthirapterasupporting
confidence: 80%
“…Tetrameres nematodes are the important members of suborder Spirurina nematodes, which known as the ‘avian stomach nematodes’. Tetrameres nematodes are the etiological agents of tetrameriosis in poultry, and they may also infest wild birds, including penguin ( Fink et al, 2004 ; González-Acuña et al, 2020 ; Werneck et al, 2020 ). Mature female worms are blood-red colored with a special subspherical morphology, as they lie embedded in the crypts of Lieberkühn while feeding on blood.…”
Section: Introductionmentioning
confidence: 99%